209k views
5 votes
Write the following rational expression in lowest term

User Igorbel
by
5.3k points

1 Answer

1 vote

Given rational expression is


(t^2-4)/(6t-12)

Factor the numerator and denominator first.


\begin{gathered} t^2-4=t^2-2^2 \\ =(t+2)(t-2) \end{gathered}

Factor the denominator 6t-12:


\begin{gathered} 6t-12=6t-6\cdot2 \\ =6(t-2) \end{gathered}

So,


\begin{gathered} (t^2-4)/(6t-12)=((t+2)(t-2))/(6(t-2)) \\ =(t+2)/(6) \end{gathered}

Therefore, the given expression in lowest form is


(t+2)/(6)

User Rhemmuuu
by
5.1k points